Motivasi Menulis Artikel Ilmiah Bagi Guru Pendidikan Jasmani Se Kecamatan Gunungpati - S, Adi; Darmawan, Agus; Soenyoto, Tommy; Arbanisa, Wahyu; Puspitaningrum, Dita Cahya; Septian, Immanuel Berli (Universitas Nusantara PGRI Kediri, 2023)
Teachers must write scientific papers as an essential part of their professional development. Scientific papers are reports or writings on the study of a problem by a person or team by fulfilling scientific, ethical rules that are confirmed and adhered to by the scientific community. By conducting scientific publications, a person can develop knowledge and disseminate that knowledge to the public. Respondents stated that they experienced difficulties in writing scientific articles and agreed that training in writing scientific articles should be held. In addition to getting promotions, positions, and classes, writing scientific papers will be used to measure success and show professionalism. The methods used in this service activity are lectures, discussions, and questions and answers. The motivation to write scientific articles for physical education teachers in the Gunungpati sub-district was well implemented. Teachers must write scientific papers as an essential part of their professional development. The suggestion for the next service is to oversee from submit to publish. Teachers who come to the training are expected to bring data that will be analyzed and refined. Appreciation should be given to participants who carry out activities well. Finally, teachers find it easy to compile scientific papers.